Unveiling the population structure and breeding patterns of Petrolisthes boscii (Audouin, 1826) a common intertidal inhabitant of Shivrajpur, Saurashtra Coast, Gujarat - Patel, Nayan; Patel, Krupal J.; Patel, Ashish; Ali, Daoud; Alarifi, Saud; Trivedi, Jigneshkumar N. (Frontiers in Marine Science, 2024)
The present study focused on investigating the population structure and breeding biology of a species of Porcellanid crab, Petrolisthes boscii (Audouin, 1826). Evaluating the population ecology of the species is essential considering its crucial role in ecological functions including the nutrition cycle and its potential vulnerability to environmental stressors. The samples were collected over a period of 12 consecutive months (from March 2019 to February 2020) in an area of 500 m2 during low tide, utilizing the catch-per-unit-effort (CPUE) method when the water receded. The collected specimens (859 individuals) were categorized into males (407 individuals), non-ovigerous females (452 individuals), and ovigerous females (303 individuals). The assessment of fecundity was conducted by measuring the egg characteristics, including the total number, size, and weight of the eggs, as well as the carapace width of the ovigerous females. There was an evident difference in size, with males (8.60 ± 2.76) being significantly larger compared to females (8.39 ± 2.46) (p < 0.001). The overall and monthly sex ratios were female-biased (1:1.17). Moreover, the size frequency distribution revealed a bimodal distribution in male as well as female individuals. Ovigerous females occurred in all the months, which shows that the species breeds continuously throughout the year, with peaks in the months of March to May and August to October. There was a significant positive relationship observed among the size of ovigerous females and their total number of eggs (130.39 ± 83.31), egg mass weight (150 ± 110 mg). The study may provide baseline information for future studies on the impacts of a continuously altering environment and the consequences of increasing anthropogenic pressure on coastal areas.